Symptom Clusters and Health-related Quality of Life in Chinese patients with Chronic Obstructive Pulmonary Disease. (June 2020) - Wu, Maochun; Zan, Tao; Zhao, Qiheng; Ge, Song; Li, Kun; Li, Junxin
This study aimed to identify symptom clusters of chronic obstructive pulmonary disease (COPD) and to examine the relationship between symptom clusters and health-related quality of life (HRQoL). It included 154 hospitalized patients with COPD. The majority of the participants (88.6%) were aged 60 years and above, and the numbers of men and women were approximately equal (men: 55.2%). The Charlson Comorbidity Index (CCI), the Memorial Symptom Assessment Scale (MSAS), and the Chinese version of the Clinical COPD Questionnaire (CCQ) were used to evaluate comorbidity, participant's symptoms, and HRQoL, respectively. Five symptom clusters were identified using exploratory factor analysis, and symptom clusters, especially the Psychological, Pain and Fatigue, GI, and Dyspnea-Sweat symptom clusters, had negative effects on HRQoL in patients with COPD. Understanding the patterns and occurrences of symptom clusters could be essential for developing effective interventions to manage COPD symptoms and improve the patients' HRQoL.